Prevalencia de micosis superficiales intergitales en una muestra de corredores de la “Maratón Popular de Madrid” - Losa Iglesias, Marta; Gómez Delgado, Marta; Fuentes Rodríguez, Miguel (Revista Internacional de Ciencias Podológicas, 2007)
In this study it was tried to evaluate the incidence of interdigital superficial mycosis (tinea pedis) in the participant runners in the Popular Marathon of Madrid. The evaluation consisted of a collection of observed data of the foot, together with a dermatological examination with Wood lamp in 4º interdigital space and takes mycological culture, to 66 individuals, runners with ridge in the MAPOMA. The obtained microbiological results were, Trichophytum and Yeast was the prevalent in the sample, and that are in many cases in association with another pathogen, and that almost 90% of the total sample presented 4º interdigital space pathogenic and/or polluting. Therefore, the tinea pedis and interdigital candidiasis, in sportsmen is a risk factor to consider on the part of the podologyst, since is present of silent form and in many occasions it does not have the suitable treatment.